Forest Policy Reform in Brazil - Simone Bauch; Erin Sills; Luiz Carlos Estraviz Rodriguez; Kathleen McGinley; Frederick Cubbage (Journal of Forestry, 2009)
Rapid deforestation in the Brazilian Amazon, caused by economic, social, and policy factors, has focused global and national attention on protecting this valuable forest resource. In response, Brazil reformed its federal forest laws in 2006, creating new regulatory, development, and incentive policy instruments and institutions. Federal forestry responsibilities are maintained within the ministry of the environment; its regulatory agency responsibilities are divided among three different branches of the agency; many powers are delegated to states and municipalities; and a new private concession system is being developed. These reforms offer promise to improve forest protection and management in Brazil but must overcome significant institutional and social resistance for success.